2019
DOI: 10.3390/ma12101586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cast-Iron Surface Texturing on the Anti-Scuffing Performance under Starved Lubrication

Abstract: Advances in heavy-duty diesel engine designs place higher demands on the friction and wear performance of the piston ring and cylinder liner (PRCL) interface. The potential of using micro-textures machined on the whole stroke of a cast-iron cylinder liner was investigated in this work. A set of running-in and starved lubrication experiments was performed using a custom reciprocating test rig that imparts a combination of combustion-level pressures and the resulting impacts. Based on a comparison of micro-dimpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Friction and wear tests were performed as reported earlier using a piston ring reciprocating cylinder liner test rig which can simulate the cyclic impacts of peak cylinder pressure [30,31]. The experimental conditions are shown in Table 1.…”
Section: Friction and Wear Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Friction and wear tests were performed as reported earlier using a piston ring reciprocating cylinder liner test rig which can simulate the cyclic impacts of peak cylinder pressure [30,31]. The experimental conditions are shown in Table 1.…”
Section: Friction and Wear Testsmentioning
confidence: 99%
“…The analyzed area was approximately 400 µm × 300 µm. Spectral data processing was performed using the Avantage program with the subtraction of a Smart-type background and mixed Gaussian-Lorentzian peaks, with 30% Lorentzian character (GL (30)), fitted to the raw data. After fitting the data, the x-axis of all spectra was charge-calibrated to the C-C component in the C1s fit at 284.8 eV.…”
Section: Friction and Wear Testsmentioning
confidence: 99%
“…The authors of the work [ 22 ] showed that the operating parameters of the gears, such as temperature and lubrication behavior may affect the meshing losses. A scuffing behavior in a cylinder liner with different micro-dimpled textures was the subject of the study [ 23 ]. They indicated the influence of the selected geometric parameters (diameter, area fraction) of a micro-dimple on the friction coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…A commonly used method of improving the tribological properties of steels is through surface treatments. The treating of steel surfaces encompasses a wide range of methods that modify the composition and/or microstructure of the near-surface material or alter the surface topography [101,102]. Surface treatments for steels can be separated into several categories, including the creation of diffusion layers, recasting of layers, surface texturing, and mechanical cold-working [72,79,101].…”
Section: Surface Treatmentsmentioning
confidence: 99%
“…Texturing of steel surfaces involves introducing intentional features such as dimples and grooves to steel surfaces [104]. The texturing of surfaces is beneficial in preventing scuffing due to the surface features acting as lubrication reservoirs, storing wear debris to avoid abrasive wear, and decreasing the area of contact between mated surfaces [79,102]. Surface texturing can be achieved with multiple methods, including electrolyte jets, laser ablation, and mechanical grinding of the surfaces with abrasive materials [62,102,104].…”
Section: Surface Treatmentsmentioning
confidence: 99%